Body images and quality of life at work: Organizational challange - Rosario Nieves, Ilia Cristina (2009)
The relationship between the body image and the quality of life at work was analyzed in a sample of hard- working women in Puerto Rico. . A hundred of women, among 21 and 50 years old, were measured with the Spanish version of Body Esteem Scale for Adolescents and Adults (BESAA) (∞= .89) and the Work related Quality of Life Scale (∞ = .96). Results confirmed that there is a relation between body esteem and quality of life at work, highlighting their importance to a betterorganizational affectivity (r = .360, n = 100, p≤ .05). Body esteem as well as quality of life at work, as multidimensional factors, integrate each other by emphasizing their own satisfaction and their influence in the work environment.